Structure of the murine leukemia virus envelope glycoprotein precursor. - Witte, O N (1979)
The glycosylated env gene precurosr (Pr80env) of Moloney murine leukemia virus has been isolated by selective immunoprecipitation. Use of the drug tunicamycin to inhibit nascent glycosylation or specific cleavage with endoglycosidase H demonstrated that the precursor contained an apoprotein with a molecular weight of 60,000. The finished virion glycoprotein (gp70) was largely resistant to the action of endoglycosidase H. Chromatography of the glycopeptides of Pr80env in conjunction with endoglycosidase H digestion studies suggested that the precursor contained two distinct major glycosylation sites. Analysis of partial proteolytic cleavage fragments of Pr80env before and after endoglycosidase H treatment placed the two glycosylation sites within a 30,000-dalton region of the apoprotein sequence. Kinetic experiments showed that carbohydrate processing as well as proteolytic cleavage are late steps in the maturation of Pr80env.